SARS-CoV-2 Infection is Protease-Dependent and Induces Neutrophils “Proteolytic Storm” Triggering Clinical Worsening and Viral Sepsis. Proteolysis and Inhibitors of Neutrophil Release Can Prevent and Treat Covid-19 - Fornasari, Pier Maria (Edelweiss Applied Science and Technology, 2020)
Based on Chinese CDCP report on COVID-19, 14% of patients presented severe disease and 5% critical conditions. The average case-fatality rate was 2.3%, but mortality was as high as 49% in patients with critical illness. Serious life threatening thromboembolic complications have been found in 71.4% of non-survivors and micro/macro angiopathic coagulopathy has been found, at autopsy also, with highly increased neutrophil number, fibrinogen, concentrations of D-dimer and FDPs and NETs, ATIII decrease and normal number of platelets. A cytokine storm and interaction between inflammation and coagulation has been advocated as explanation of hypercoagulability. It has been shown that SARS-CoV-2 infection of alveolar cells is driven by the S-protein by engaging ACE2 and TMPRSS2 cell receptors. Whose activation depends on the activity of various host proteases. Full inhibition of SARS-CoV-2 entry was observed when serine proteases inhibitor camostat mesylate was coupled with Cathepsin B/L inhibitor E-64d. In addition multiple proteases are involved in host immune response against viral invasion and immunopathology related to imbalanced immune activation. In this paper it’s hypothesized that the severity of Covid-19 is induced by recruitment of innate responder neutrophils, which release proteases and NETs inducing endothelial damage and imbalance of the four major proteolytic cascades (coagulation, complement, fibrinolysis and kallikrein) with prevalence of activators over inhibitors and consequent thrombotic complications. Platelets adhesion to damaged endothelium and vWFVIII multimers presence, due to loss of ADAMTS13, contributes to hypercoagulability state. Human plasma or serine protease inhibitors like aprotinin can help to control neutrophil induced “proteolytic storm”. The goal of this paper is to support the view that, in SARS-CoV-2 infection, proteases have a key role and exceeding imbalanced neutrophil innate “unfriendly fire” response can be identified as the trigger of a “proteolytic storm”, responsible for subsequent well known hyper coagulation and “cytokine storm” and human plasma, in adequate volumes, together with serine proteases inhibitors can be an effective therapeutic strategy.